The Relationship Between Stress and Resilience of Nurses in Intensive Care Units During the COVID-19 Pandemic - Ibrahim Aqtam PhD; Ahmad Ayed PhD; Dalia Toqan PhD; Basma Salameh PhD; Eman Sameh Abd Elhay PhD; Kefah Zaben PhD; Mustafa Mohammad Shouli PhD (SAGE Publishing, 2023)
The coronavirus infection COVID-19 has been a risk to world health, particularly for individuals who are vulnerable to it. Critical care nurses have described experiencing extremely high levels of stress under these struggling conditions. This study aimed to assess the relationship between stress and resilience of intensive care unit nurses during the COVID-19 pandemic. A cross-sectional study was conducted on 227 nurses who are working in the intensive care units in the West Bank hospitals, Palestine. Data collection utilized the Nursing Stress Scale (NSS) and the Brief Resilient Coping Scale (BRCS). Two hundred twenty-seven intensive care nurses completed the questionnaire; (61.2%) were males, and (81.5%) had documented COVID-19 infection among their friends, family, or coworkers. Most intensive care nurses reported high levels of stress (105.9 ± 11.9), but low levels of resilience (11.0 ± 4.3). There was a moderate negative correlation between nurses' stress and their resilience ( P  < .05) and a small to moderate negative correlation between nurses' stress sub-scales and resilience ( P  < .05). Also, the results revealed a statistically significant difference between the stress score mean and the nurses who had documented COVID-19 infection among their friends, family, or coworkers ( P  < .05), and between the resilience mean score and the nurses' gender ( P  < .05). During the COVID-19 outbreak, intensive care nurses' stress levels were high, and their resilience was low. Thus, controlling nurses' stress levels and identifying possible stress sources related to the COVID-19 pandemic are important to maintain patients' safety and improve the quality of care.